Movie workers : the women who made British cinema - Bell, Melanie (Women and film history international., 2021)
"After the advent of sound, women in the British film industry formed an essential corps of below-the-line workers, laboring in positions from animation artist to negative cutter to costume designer. Melanie Bell maps the work of these women decade-by-decade, examining their far-ranging economic and creative contributions against the backdrop of the discrimination that constrained their careers. Her use of oral histories and trade union records presents a vivid counter-narrative to film history, one that focuses not only on women in a male-dominated business, but on the innumerable types of physical and emotional labor required to make a motion picture. Bell's feminist analysis looks at women's jobs in film at important historical junctures while situating the work in the context of changing expectations around women and gender roles. Illuminating and astute, this book is a first-of-its-kind examination of the unsung women whose invisible work brought British filmmaking to the screen"--